2020
DOI: 10.3389/fnut.2020.613221
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Foods on Blood Lipids in Non-alcoholic Fatty Liver Disease (NAFLD)—A Systematic Review and Meta-Analysis

Abstract: Background: Non-alcoholic fatty liver disease (NAFLD) is associated with dyslipidemia and increased cardiovascular disease risk. Dietary choices may produce profound effects on blood lipids. Thus, the purpose of this study was to investigate which foods modify blood lipids in NAFLD.Methods: Systematic review of published systematic reviews and randomized controlled trials (RCTs). Searches were performed in PubMed, Cochrane Database of Systematic Reviews, and Cochrane Central Register of Controlled Trials, from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
2
0
1
Order By: Relevance
“…There was no evidence from the studies included in the current qualitative synthesis that any dietary pattern was superior over their comparator with regards to components of the metabolic syndrome or concentrations of liver enzymes. A recent systematic review that examined the effect of foods and dietary patterns in blood lipid concentrations among adults with NAFLD who do not receive lipid-lowering medication found similar results [39]. This review included a pooled analysis of two randomised controlled trials that examined the effect of the Mediterranean diet against a low-fat diet, including a study that was included in the current review [30], and showed no effect on HDLcholesterol (-0.08 mmol/L, 95% CI = -0.27 to 0.12) or triglyceride concentrations (-0.04 mmol/L, 95% CI -0.38 to 0.31) [39].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…There was no evidence from the studies included in the current qualitative synthesis that any dietary pattern was superior over their comparator with regards to components of the metabolic syndrome or concentrations of liver enzymes. A recent systematic review that examined the effect of foods and dietary patterns in blood lipid concentrations among adults with NAFLD who do not receive lipid-lowering medication found similar results [39]. This review included a pooled analysis of two randomised controlled trials that examined the effect of the Mediterranean diet against a low-fat diet, including a study that was included in the current review [30], and showed no effect on HDLcholesterol (-0.08 mmol/L, 95% CI = -0.27 to 0.12) or triglyceride concentrations (-0.04 mmol/L, 95% CI -0.38 to 0.31) [39].…”
Section: Discussionmentioning
confidence: 84%
“…A recent systematic review that examined the effect of foods and dietary patterns in blood lipid concentrations among adults with NAFLD who do not receive lipid-lowering medication found similar results [39]. This review included a pooled analysis of two randomised controlled trials that examined the effect of the Mediterranean diet against a low-fat diet, including a study that was included in the current review [30], and showed no effect on HDLcholesterol (-0.08 mmol/L, 95% CI = -0.27 to 0.12) or triglyceride concentrations (-0.04 mmol/L, 95% CI -0.38 to 0.31) [39]. In contrast, our post hoc pooled analysis indicated greater reductions in triglyceride concentrations with a Mediterranean diet, compared to a low-fat diet, which is similar to the findings of a recent meta-analysis on the effect of this dietary pattern on metabolic health [40].…”
Section: Discussionmentioning
confidence: 84%
“…Considera-se que o consumo de dieta hiperlipídica (ou de cafeteria), é um dos fatores que contribuem para o desenvolvimento de sobrepeso e obesidade, tendo em vista que este tipo de dieta ocidentalizada possui alta taxa calórica e promove o acúmulo de gordura corporal, que por sua vez, resulta em aumento de massa corporal 19,20 .…”
Section: Dieta Hiperlipídica Sobrepeso E Obesidadeunclassified